HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENCEGAHAN COVID-19 PADA MASA ADAPTASI KEBIASAAN BARU - Nissa Noor Annashr; Puji Laksmini; Andy Muharry; Teni Supriyani; Rian Arie Gustaman (Universitas Pahlawan, 2021)
In October 2020, West Java became the province with the third highest positive confirmed case of COVID-19 in Indonesia, with 33,147 cases with a death of 649. The purpose of this study was to analyze the relationship between knowledge and attitudes with COVID-19 prevention behavior. This research iwa an analytic observational study with a cross sectional study design. The study was conducted in September 2020. The study population was people aged 12 years living in West Java Province. The sample in this study amounted to 2,502 people. The sample was people who are willing to fill out a questionnaire that is distributed online (google form) via whatsapp, instagram and facebook so that the sampling technique includes accidental sampling. The independent variables studied consisted of knowledge and attitudes, while the dependent variable was COVID-19 prevention behavior during (habit of keeping distance, washing hands with soap, using masks). The results of univariate analysis showed that more than half of the respondents had good knowledge (56.8%) and positive attitudes (54.6%). The majority of respondents had good COVID-19 prevention behavior (73.3%). The results of the bivariate analysis showed that there was a significant relationship between knowledge and attitude variables with COVID-19 prevention behavior (p 0.05). The OR value for the knowledge variable is 1.933 (95% CI: 1.616-2.312). Meanwhile, the OR value for the attitude variable is 3.067 (95% CI: 2.523-3.729). This study proves that knowledge and attitudes are significantly related to COVID-19 prevention behavior.Â